2022
DOI: 10.47115/bsagriculture.1088157
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Micropropagation of Maintainer White Head Cabbage Lines Using Cotyledon And Hypocotyl Explants

Abstract: Brassica species are the most widely cultivated vegetable crops and improvement programs started in the last thirty years in Türkiye. Hybrid seed production is very difficult for Brassica vegetable species. Because the production of a new F1 hybrid cultivar needs a male sterile line (A), maintainer line (B), and also a male line (C). Biotechnological methods provide an excellent opportunity for new F1 hybrid cultivar improvement via in vitro maintenance of the breeding lines. Thus, in vitro propagation possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…It is well established that the kind and concentration of cytokinins applied exogenously significantly affect the success of the in vitro propagation protocol [20,21]. Furthermore, several studies indicated the positive effects of cytokinins on the shoot proliferation from hypocotyl explants [22][23][24][25]. In the current study, the addition of a low concentration of NAA (1.0 µM) with the identified optimum concentration of BA (7.5 µM) increased the response of the hypocotyl explants of M. crassifolia.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the kind and concentration of cytokinins applied exogenously significantly affect the success of the in vitro propagation protocol [20,21]. Furthermore, several studies indicated the positive effects of cytokinins on the shoot proliferation from hypocotyl explants [22][23][24][25]. In the current study, the addition of a low concentration of NAA (1.0 µM) with the identified optimum concentration of BA (7.5 µM) increased the response of the hypocotyl explants of M. crassifolia.…”
Section: Discussionmentioning
confidence: 99%